Analysis of the evolution of neurosurgical management and diagnostic methods with a genetic emphasis for Moyamoya Syndrome (Research, Society and Development, 2022)
Introduction: Moyamoya syndrome or disease is a very rare cerebrovascular disorder that predisposes affected individuals to transient or permanent ischemic attacks due to progressive stenosis of the internal carotid artery and its branches, which causes compensatory responses, a large number of smaller blood vessels begins to grow and proliferate. Method: systematic literature review of the quantitative type using the following platforms: PubMed, SciELO, Google Scholar, Revista Brasileira de Neurocirurgia and Jornal Americano de Neurocirurgia. Results and Discussion: Catheter-based diagnostic cerebral angiography is the gold standard for obtaining a diagnosis. One study observed the presence of genetic expectations and concluded that females are the most affected in families (DMMs). Genome and locus-specific studies were performed by Kamada et al. (RNF213) was found as the first susceptibility gene for (DMM). Therefore, (p.R4859K) was recorded as the founder of the missense mutation in (RNF213), patients usually develop symptoms of (stroke) due to cerebral ischemia. Angiogenesis of collateral vessels within the basal ganglia can lead to dyskinesia. MRI enabled rapid detection of acute ischemic stroke using weighted imaging. Conclusion: Moyamoya syndrome is an occlusive cerebrovascular disease that has the potential to cause stroke, epilepsy and neurological dysfunction in adults and children. however, surgical intervention can prevent an upward progression of the disease.